Growth and resilience responses of Scots pine to extreme droughts across Europe depend on predrought growth conditions. (8th June 2020) - Bose, Arun K.; Gessler, Arthur; Bolte, Andreas; Bottero, Alessandra; Buras, Allan; Cailleret, Maxime; Camarero, J. Julio; Haeni, Matthias; Hereş, Ana‐Maria; Hevia, Andrea; Lévesque, Mathieu; Linares, Juan C.; et al.
Abstract: Global climate change is expected to further raise the frequency and severity of extreme events, such as droughts. The effects of extreme droughts on trees are difficult to disentangle given the inherent complexity of drought events (frequency, severity, duration, and timing during the growing season). Besides, drought effects might be modulated by trees' phenotypic variability, which is, in turn, affected by long‐term local selective pressures and management legacies. Here we investigated the magnitude and the temporal changes of tree‐level resilience (i.e., resistance, recovery, and resilience) to extreme droughts. Moreover, we assessed the tree‐, site‐, and drought‐related factors and their interactions driving the tree‐level resilience to extreme droughts. We used a tree‐ring network of the widely distributed Scots pine ( Pinus sylvestris ) along a 2, 800 km latitudinal gradient from southern Spain to northern Germany. We found that the resilience to extreme drought decreased in mid‐elevation and low productivity sites from 1980–1999 to 2000–2011 likely due to more frequent and severe droughts in the later period. Our study showed that the impact of drought on tree‐level resilience was not dependent on its latitudinal location, but rather on the type of sites trees were growing at and on their growth performances (i.e., magnitude and variability of growth) during the predrought period. We found significant interactive effects between drought duration and tree growth prior to drought, suggesting that Scots pine trees with higher magnitude and variability of growth in the long term are more vulnerable to long and severe droughts. Moreover, our results indicate that Scots pine trees that experienced more frequent droughts over the long‐term were less resistant to extreme droughts. We, therefore, conclude that the physiological resilience to extreme droughts might be constrained by their growth prior to drought, and that more frequent and longer drought periods may overstrain their potential for acclimation. Abstract : We examined tree growth resilience of Scots pine along a 2, 800 km latitudinal gradient from southern Spain to north‐eastern Germany using 615 adult trees from 30 different sites. We found that the resilience of Scots pine to extreme drought decreased in mid‐elevation and low productivity sites from 1980–1999 to 2000–2011 due to more frequent and severe droughts in the later period. We showed that the impact of drought on tree‐level resilience was not dependent on its latitudinal location, but rather on the type of sites trees were growing at and on their growth performances during the pre‐drought period.